Reposisi kecerdasan Case study: mendapatkan desain yang baik, dan berdaya hidup dalam desain produk - RAMM Pandansari Kusumo (PRODUCTUM Jurnal Desain Produk (Pengetahuan dan Perancangan Produk), 2017)
Design is a plan arising from a requirement, through planning, creative ideas and ideas are treated with a combination of art, science and technology, it is expected to be born as a good design. Processing good design will produce an innovation of design that can bring a positive image to the community/market. In the era of global competition, creative behavior is not enough just to use the intelligence of the mind, but also other intelligence that it takes powerful intelligence levitation. Both will be intertwined in the search for new forms that can create trends in the world. Local intelligence has proven able to produce valuable works, this time the intelligence of knowledge is needed, not just transformation of mind, to be able to create the artwork.Keywords: design, innovation, intelligence of mind, levitation, trends